Determinants of malnutrition and associated parameters in subjects with stable chronic obstructive pulmonary disease: A cross sectional study - Srigiripura, Chandan Vinay; Sindaghatta Krishnarao, Chaya; Biligere Siddaiah, Jayaraj; Anand, Mahesh Padukudru; Urooj, Asna (The North African Journal of Food and Nutrition Research, 2023)
Background: Chronic obstructive pulmonary disease exerts local and systemic manifestations including malnutrition which has deleterious consequences on health, quality of life and survival. Nutritional status is known to impact the prognosis of COPD.Aims: An attempt was made to study the nutritional status of subjects with stable COPD using PGSGA, identify malnutrition and analyze the factors contributing to malnutrition. Patients and Methods: Using convenient sampling, 110 subjects of both sexes (105 men and 5 women) with stable COPD aged between 40 – 75 years (61 ± 9 years), visiting the Pulmonologist at JSS Hospital, Mysuru were included in the study. The subjects underwent spirometry, anthropometry, evaluation of body composition, calorie intake and health related quality of life using standard methods. Differences in the parameters between groups of subjects with varying nutritional status and association with PGSGA score were statistically evaluated. Results: Moderate to severe malnutrition was seen in 59% of the subjects. The presence of GI symptoms [OR=62.217, 95% CI (10.834-357.292)], grade 4 dyspnea [OR=67.302, 95% CI (1.287-3520.295)] and increasing disease years [OR=1.151, 95% CI (1.021-1.299)] were found to significantly increase the odds of risk of malnutrition, with very severe dyspnea showing the highest risk of malnutrition followed by presence of GI symptoms. Total SGRQ scores, activity and impact scores were significantly higher in the malnourished groups (p < 0.001). The presence of nutrition impact symptoms, seen in 50% of the subjects was associated with lower calorie intake. Severe dyspnea, severe COPDand increasing disease years increased the risk of malnutrition. However, the small sample size and single-center study may not accurately represent the true proportion of malnutrition among female COPD patients in the community. Keywords: PGSGA, COPD, Malnutrition, Pulmonary function, Dyspnea.